2017
DOI: 10.1364/prj.5.000629
|View full text |Cite
|
Sign up to set email alerts
|

Improved third-order nonlinear effect in graphene based on bound states in the continuum

Abstract: The scattering matrix theory has been developed to calculate the third-order nonlinear effect in sphere-grapheneslab structures. By designing structural parameters, we have demonstrated that the incident electromagnetic wave can be well confined in the graphene in these structures due to the formation of a bound state in the continuum (BIC) of radiation modes. Based on such a bound state, third-harmonic (TH) generation and four-wave mixing (FWM) have been studied. It is found that the efficiency of TH generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…These early works have greatly promoted the exploration of graphene-based nonlinear optics. [99][100][101][102][103][104] Based on the successful exploration of the nonlinear properties of graphene and its derivatives, researchers began to study other 2D materials, such as topological insulators, layered TMDCs, black phosphorus, and MXenes. Among them, topological insulators including Bi 2 Se 3 , Bi 2 Te 3 , and Sb 2 Te 3 , characterized by a robust metallic edge or surface state and a narrow band-gap bulk insulating state, have gained great attention in the field of physics, chemistry, and material.…”
Section: Third-order Optical Propertiesmentioning
confidence: 99%
“…These early works have greatly promoted the exploration of graphene-based nonlinear optics. [99][100][101][102][103][104] Based on the successful exploration of the nonlinear properties of graphene and its derivatives, researchers began to study other 2D materials, such as topological insulators, layered TMDCs, black phosphorus, and MXenes. Among them, topological insulators including Bi 2 Se 3 , Bi 2 Te 3 , and Sb 2 Te 3 , characterized by a robust metallic edge or surface state and a narrow band-gap bulk insulating state, have gained great attention in the field of physics, chemistry, and material.…”
Section: Third-order Optical Propertiesmentioning
confidence: 99%
“…In recent years, low‐dimensional nonlinear materials have become a research hotspot. Various types of low‐dimensional nonlinear materials with improved nonlinear responses have been reported; these materials include TiS 2 layers,23 hexagonal BN nanosheets,24,25 graphene‐based materials,26–28 and 1D CdS29 and CdTe30 quantum dots. In addition, inorganic glass and their derived composites have attracted considerable interest as nonlinear optical limiting material candidates due to their stable chemical and physical properties 31–33.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, optical bound states in the continuum (BICs) in some nanostructures have attracted extensive attention from both theoretical and experimental sides in recent years [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. The BICs are known as embedded trapped modes, which correspond to discrete eigenvalues coexisting with extended modes of a continuous spectrum [42].…”
Section: Introductionmentioning
confidence: 99%
“…A true BICs is a mathematical object with an infinite value of the Q factor and vanishing resonance width, and it can exist only in ideal lossless structures [28][29][30]. In practice, BICs can be realized as a quasi-BICs, when both the Q factor and resonance width become finite [38][39][40][41]. Recent investigations have shown that the quasi-BICs with high-Q factor can be realized in some optical nanostructures [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation